Right-dominant contextual cueing for global configuration cues, but not local position cues. (7th January 2023) - Pollmann, Stefan; Zheng, Lei
Abstract: Contextual cueing can depend on global configuration or local item position. We investigated the role of these two kinds of cues in the lateralization of contextual cueing effects. Cueing by item position was tested by recombining two previously learned displays, keeping the individual item locations intact, but destroying the global configuration. In contrast, cueing by configuration was investigated by rotating learned displays, thereby keeping the configuration intact but changing all item positions. We observed faster search for targets in the left display half, both for repeated and new displays, along with more first fixation locations on the left. Both position and configuration cues led to faster search, but the search time reduction compared to new displays due to position cues was comparable in the left and right display half. In contrast, configural cues led to increased search time reduction for right half targets. We conclude that only configural cues enabled memory-guided search for targets across the whole search display, whereas position cueing guided search only to targets in the vicinity of the fixation. The right-biased configural cueing effect is a consequence of the initial leftward search bias and does not indicate hemispheric dominance for configural cueing. Highlights: Repeated visual search configurations led to larger search facilitation in the right display half. This facilitation was due to a leftward search bias countered by configural cues guiding search to the right display half. Unlike configural cueing, search guidance by item location was only local, it yielded no laterality differences. In contrast to traditional laterality studies, these effects were observed during free viewing.